Annona muricata's Leaves Ethanolic Extract Enhance p53 Expression in Rat Hepatic Cells Induced by Dimethylbenz(a)Anthracene (DMBA) - Rosa Adelina; Intan Sari Oktoberia; Putri Reno Intan (Indonesian Journal of Cancer Chemoprevention, 2013)
Annona muricata or soursop contains acetogenin which can induce apoptosis in vitro and has cytotoxic effect. The study has been done to examine soursop leaves extract’s potency in vivo especially to induce apoptosis in 7,12-Dimethylbenz[a]anthracene (DMBA)-induced Sprague Dawley rats. The induction process was done twice a week for five weeks. The soursop leaves extract were given in three dosages, that are 200, 400, and 800 mg/kgBW for seventeen days after two weeks DMBA induction. Data analysis showed that Annona muricata leaves ethanolic extract could enhance p53 pathway significantly with a dose independent manner in DMBA-induced rats.Keywords: Proapoptosis,  Annona muricata leaves ethanolic extract, hepatoma